Anti‐inflammatory properties of an aldehydes‐enriched fraction of grapefruit essential oil. Issue 3 (18th January 2023) - Nikolic, Dragana; Bosco, Liana; Moschetti, Marta; Tinnirello, Vincenza; Pucci, Marzia; Corleone, Valeria; Raimondo, Stefania; Alessandro, Riccardo; Fontana, Simona
Abstract : Abstract: Chronic inflammation is linked to the development of numerous diseases and is accompanied by increased cytokine secretion. Macrophages provide a first line of defense against pathogens that under inflammatory stimuli release pro‐inflammatory cytokines. The essential oil (EO) fractions obtained from Citrus spp. rich in different compounds have gained the attention of both researchers and users during the last decades. In particular, grapefruit ( Citrus paradisi ) peel is rich in phenolics and flavonoids with several health benefits, including anti‐inflammatory actions. Additionally, its EO consists of a large number of compounds such as monoterpenes, sesquiterpenes, alcohols, aldehydes, esters, and oxides. Among the methods for encapsulating EOs, spray‐drying is the main one. In the present study, we aimed to determine the in vitro anti‐inflammatory activity of EO from C. paradisi (grapefruit essential oil [GEO]) (whole and fractions) in a lipopolysaccharide (LPS)‐induced inflammation model. Results indicate that Fr‐GEO and Fr‐GEO_SD exert protective effects against LPS‐induced inflammation by decreasing gene expression and levels of pro‐inflammatory cytokines as IL‐6 and TNF‐α. Monoterpenes as the most common components, as well as aldehydes and sesquiterpenes, might be responsible for such effects, although a synergistic action is not excluded. Furthermore, a higher percent of aldehydes is linked to improved olfactory properties. Our findings support the anti‐inflammatory effects of selected Fr‐GEO with a great potential for the development of new nutraceuticals and/or functional food for the treatment of inflammatory‐associated diseases. Practical Application: The findings of this study support the anti‐inflammatory effects of selected Fr‐GEO with a great potential for the development of new nutraceuticals and/or functional food for the treatment of inflammatory‐associated diseases.